Penguatan Pendidikan Karakter Siswa SD Negeri 4 Teluk Melalui Kegiatan Bercerita Kepahlawanan Jenderal Soedirman - Nia Ulfa Martha (Serambi Abdimas, 2023)
The strengthening of character education is essential to overcome the various problems of moral and behavioral deviations that occur in our daily lives. This situation is also related to the behavioral deviations of some students at SD Negeri 4 Teluk. These deviations include loss of respect for parents, brawls between students, loss of honesty, weak creativity, responsibility, and various moral and behavioral damages that have become common problems and contribute to the occurrence of problems in the community. General Soedirman is one of the heroes who can be used as an example in strengthening character education. The purpose of this character education strengthening activity is that students can apply the noble values and example of the Commander-in-Chief General Soedirman. This activity is carried out in two stages, namely preparation and strengthening character education with the storytelling method. Community service at SD Negeri 4 Teluk with a target of 35 VA class students is considered successful. This success can be seen in the results of the students' summary after listening to the heroic story of General Soedirman. Based on this, it can be concluded that students can emulate the figure of the Commander-in-Chief General Soedirman.